PHYSICOCHEMICAL PROPERTIES OF B-0 CN 51 DIESEL FUEL WITH ULTRAFINE BUBBLES - Husen Asbanu; Sam Herodian; Tineke Mandang; Anto Tri Sugiarto; Riesta Anggarani (Testing Center for Oil and Gas LEMIGAS, 2025)
Ultrafine bubbles are nano-sized, much smaller than regular bubbles, and efficient in gas exchange processes, making them reactive in physical and chemical processes. The application of ultrafine bubbles includes medicine, agriculture, cleaning, and diesel engine fuels. The objective of this research is to analyze the impact of ultrafine bubble additives injected into B-0 CN 51 diesel fuel to enhance fuel performance. The research method involves injecting oxygen additives at flow rates of 1, 3, and 5 liter/minute into 1.5 liters of fuel for treatment durations ranging from 10 to 60 minutes. Observation parameters include distillation, cetane number, density, flash point, and cloud point. The results of oxygen injection at 1 liter/minute for 10 minutes found the highest values for viscosity at 2.65 mm²/s, density at 813,7 kg/m³, distillation at 341,2°C, cloud point at 7°C, and flash point at 67.4°C. Conversely, oxygen injection at 5 liters/minute for 60 minutes resulted in the lowest values for viscosity at 2.53 mm²/s, density at 801.3 kg/m³, distillation at 320.7°C, cloud point at 5.4°C, and flash point at 56.2°C. Meanwhile, the cetane number increased, with the highest value of 63 observed at an oxygen injection rate of 5 liter per minute for 60 minutes, and the lowest value of 56.5 observed at an injection rate of 1 liter/minute for 10-minute This research shows that the impact of ultrafine bubbles adds value to B-0 CN 51 fuel, creating a new product considering the promising cetana number.